2010
DOI: 10.1215/00127094-2010-053
|View full text |Cite
|
Sign up to set email alerts
|

The sharp Hardy uncertainty principle for Schrödinger evolutions

Abstract: We give a new proof of Hardy's uncertainty principle, up to the end-point case, which is only based on calculus. The method allows us to extend Hardy's uncertainty principle to Schrödinger equations with non-constant coefficients. We also deduce optimal Gaussian decay bounds for solutions to these Schrödinger equations.1991 Mathematics Subject Classification. Primary: 35B05. Secondary: 35B60.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(146 citation statements)
references
References 13 publications
1
145
0
Order By: Relevance
“…Mathematical investigations of generalized uncertainty relations can be found, for example, in [11,12]. In this subsection, we derive a generalized uncertainty relation for an arbitrarily shaped quantum dot in d dimensions, by considering the nonnegative integral…”
Section: Generalized Uncertainty Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematical investigations of generalized uncertainty relations can be found, for example, in [11,12]. In this subsection, we derive a generalized uncertainty relation for an arbitrarily shaped quantum dot in d dimensions, by considering the nonnegative integral…”
Section: Generalized Uncertainty Relationmentioning
confidence: 99%
“…This is the energy-momentum dispersion relation of a fermion moving with the speed 12) and coupled to a chemical potential…”
Section: Domain Wall Boundary Conditions In (2 + 1)-dmentioning
confidence: 99%
“…We recall that unique continuation principles for the nonlinear Schrödinger equation and the generalized Korteweg-de Vries equation have been established in [9] and [10] resp. under assumptions on the solutions at two different times.…”
Section: Remarksmentioning
confidence: 99%
“…In this paper we continue our study initiated in [5] [6], and [7] on unique continuation properties of solutions of Schrödinger equations of the form (1.1)…”
Section: Introductionmentioning
confidence: 88%
“…More precisely, in [7] it was shown that there exist (complex-valued) bounded potentials V (x, t) satisfying (1.7) for which there exist nontrivial solutions u ∈ C([0, T ] :…”
Section: Introductionmentioning
confidence: 99%